2020
DOI: 10.3389/fmicb.2020.00870
|View full text |Cite
|
Sign up to set email alerts
|

Allyl Isothiocyanate (AITC) Triggered Toxicity and FsYvc1 (a STRPC Family Member) Responded Sense in Fusarium solani

Abstract: Allyl isothiocyanate (AITC) is a natural product used as a food additive. Due to its strong volatility and broad biological activity, AITC is considered as a bio-fumigant to control soil-borne fungal diseases in agriculture, creating an urgent need for evaluation of the antifungal activity of AITC. Here we study the effect of AITC on Fusarium solani growth and explore the molecular mechanisms. The results indicated that AITC causes rapid inhibition of F. solani after 5 min, hyphal deformity, and electrolyte le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…In a Fusarium solani model [ 129 ], allyl ITC also causes hyphal deformity and electrolyte leakage. A yeast-like vacuolar transient receptor potential channel regulator (FsYvc1, a STRPC family member) was shown to be involved in this mechanism behind sensitivity: loss of FsYvc1 results in hypersensitivity towards allyl ITC, accompanied by a 1.3–1.5-fold hyperaccumulation of ROS, but no changes in a variety of other tested parameters.…”
Section: Proposed Mechanisms Of the Isothiocyanate Antifungal Activitymentioning
confidence: 99%
“…In a Fusarium solani model [ 129 ], allyl ITC also causes hyphal deformity and electrolyte leakage. A yeast-like vacuolar transient receptor potential channel regulator (FsYvc1, a STRPC family member) was shown to be involved in this mechanism behind sensitivity: loss of FsYvc1 results in hypersensitivity towards allyl ITC, accompanied by a 1.3–1.5-fold hyperaccumulation of ROS, but no changes in a variety of other tested parameters.…”
Section: Proposed Mechanisms Of the Isothiocyanate Antifungal Activitymentioning
confidence: 99%
“…AITC has already been described as an antifungal and antimycotoxigenic compound (Nazareth et al., 2016; Saladino et al., 2017; Tracz et al., 2017). There are several action mechanisms proposed for this compound, including the inhibition of cell proliferation by suppression of the MAPK pathway, the damage to genetic material by the production of reactive oxygen compounds, and the inhibition of the metabolic isoenzyme glutathione S‐transferase expression (Li et al., 2020). However, with pungent taste and odor, methods are necessary to enable its application in food and raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, terpene compounds could induce ROS accumulation in hyphae, and terpenes with higher antimicrobial activity, such as anethole and gamma-terpinene exhibited a stronger ability to induce ROS accumulation ( Figure 6 ), indicating that oxidative stress caused by terpenes may trigger the interference of fennel roots in the infection process of P. capsici . Previous studies have shown that allyl isothiocyanate induced ROS accumulation in Fusarium solani ( Li et al, 2020 ). Liquiritin inhibited P. capsici mycelial growth and sporangial development and significantly induced H 2 O 2 accumulation ( Liu P. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%